Asesmen Perilaku Keja Inovatif (Innovative Work Behaviour) Dosen Perguruan Tinggi Swasta di Kota Medan - Giovanni Paulo Anggito Sipayung (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
This assessment aims to determine whether innovative work behavior is influenced by perceived organizational virtuousness, which is moderated by the thriving character of lecturers at universities. The assessment was done with questionnaires from 205 lecturers as respondents who work at 24 private universities in Medan City, North Sumatra. A Likert scale was used to measure each research variable. Data analysis used the structural equation modeling-partial least squares (SEM-PLS) statistical method with the SmartPLS 4 application for Windows. The results showed that the innovative work behavior of lecturers at private universities is significantly influenced by perceived organizational virtuousness. The more an organization is perceived as virtuous, the more innovative lecturers will be in their work behavior while fulfilling the duties of the Tri Dharma of Higher Education.